The attochemistry of chemical bonding. Issue 3 (3rd July 2021) - Bag, Sampad; Chandra, Sankhabrata; Ghosh, Jayanta; Bera, Anupam; Bernstein, Elliot R.; Bhattacharya, Atanu
Abstract : Traditionally, over the last century, approaches used to elucidate the ' static ' and the ' dynamic ' nature of chemical bonding have been fundamentally different. The ' static ' nature of chemical bonding has been explored using either valence bond or molecular orbital theory with the time-independent atomic or molecular orbitals. The ' dynamic ' nature of chemical bonding, on the other hand, has been explored under the name 'chemical dynamics' through the notion of a transition state (rearrangement of nuclei). Understanding of the 'dynamic' nature of chemical bonding could, however, be developed through a time-dependent change of atomic and molecular orbitals (or broadly the time-dependent electron density). In the present review article, we have presented our state-of-the-art understanding of attosecond dynamics of chemical bonding from a general chemical point of view. We have demonstrated our viewpoints on dynamics of covalent and noncovalent bonds using both time-dependent natural bond orbital and canonical molecular orbitals. Finally, we have demonstrated the efficacy of high harmonic generation spectroscopic investigation to decipher attosecond charge migration through noncovalent bonds. Several chemically important systems, in which attosecond dynamics can play an important role, are discussed.